Tracheal Stenosis Because of Wegener Granulomatosis Misdiagnosed as Asthma. Issue 10 (15th May 2016) - O'Hear, Kelley E.; Ingrande, Jerry; Brodsky, Jay B.; Morton, John M.; Sung, Chih-Kwang
Abstract : We describe a patient with Wegener granulomatosis whose complaint of wheezing was incorrectly attributed to asthma. Anesthesiologists must recognize that tracheal stenosis is extremely common in Wegener granulomatosis and can mimic other causes of wheezing.